GRAVITY AND MAGNETIC TOMOGRAPHY: FORMATION AND PROSPECTS OF DEVELOPMENT - VYZHVA, S.; PRODAIVODA, G.; HRYSHCHUK, P. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
A new gravity and magnetic tomography method of geological interpretation is developed. Technology is founded on renewal of structural-material composition of geological media and its density and magnetization properties. A method provides the most complete consideration of a priori geological information and construction of three-dimensional geological model. Development provides the consideration of heterogeneous magnetization effects of geological structure elements.